DEVELOPMENT OF MANAGEMENT INFORMATION SYSTEM IN MASTER STUDY PROGRAM ON EDUCATION MANAGEMENT GRADUATE PROGRAM OF JAKARTA STATE UNIVERSITY - Dwi Deswary; Ary Sutanto (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This research aims to find out descriptively about: the needs of management information systems in the Master Program of Education Management Graduate School, State University of Jakarta (UNJ), planning of management information system model that needed, the development of management information system model, and testing of management information system model. The method used is research and development. Data collected by observation, interview, documentation study, and audio-visual material. The research findings inform that in the Master program study of Education Management, data management and information currently been carried out using information systems as processing and storage of data and information. Needs that exist in the course include the need for tools, software, and human resources. Needs in the form of equipment such as computers, networks, and other support tools have been prepared. Software requirements include information system software. While human resources need such as the provision of administrative and IT staff that competent for the job. Planning includes the design objectives, aspects of education management, procedures, and design models. The design model consists of design of data flowchart and structure menu that illustrates the systems and sub-systems of the information system that designed. Development of the model is done by developing a few things like the development of graphic design, engineering source code, local webserver installation, and design layout. Development is based on the needs analysis and planning. Tests carried out in three stages. The first phase was conducted to test the way of supporting components on the local computer system. The second phase was conducted to test the way of the system designed after being embedded on a local webserver. The third phase is done to test the way of the overall information system.